Blugold Seminar and Transfer of Writing Skills Across Disciplines - Yang, Hlee (My University, 2013)
The purpose of this study was to better understand how skills and information learned in the Blugold Seminar transfers to other courses and disciplines as well as how the Blugold Seminar affects students writing and academic abilities.
Color poster with text and images.
Keywords: Blugold Seminar--Wisconsin--Eau Claire; Composition (Language arts)--Study and teaching (Higher); Interdisciplinary approach to education; University of Wisconsin--Eau Claire; Posters